2021
DOI: 10.1016/j.clnu.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of donor human milk on host-gut microbiota and metabolic interactions in preterm infants

Abstract: Background & aims: Human milk is the gold standard for infant nutrition. Preterm infants whose mothers are unable to provide sufficient own mother's milk (OMM), receive pasteurized donor human milk (DHM). We studied metabolic signatures of OMM and DHM and their effect on the interplay of the developing microbiota and infant's metabolism. Methods: Metabolic fingerprinting of OMM and DHM as well as infant's urine was performed using liquid chromatographyemass spectrometry and the infant's stool microbiota was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…The finding that high MOM intake was associated with significantly better outcomes joins two recent observational cohort studies of EHM-fed VLBW infants, 2 , 3 which compared health outcomes for predominantly MOM-fed versus predominantly PDHM-fed infants. Taken together, the three studies found that predominantly MOM-fed infants had better clinical outcomes, 1 , 3 healthier microbiome colonization 1 , 2 , 3 including potential modulation of the negative impact of antibiotic exposure, 1 , 3 and improved metabolic/metabolomic profiles 2 than primarily PDHM-fed infants. Furthermore, predominantly PDHM-fed infants had slower and/or impaired growth, 1 , 3 including higher rates of head circumference measures below the third percentile, 3 higher rates of bronchopulmonary dysplasia 3 , and altered pyrimidine and steroid pathways.…”
Section: Main Textmentioning
confidence: 55%
See 2 more Smart Citations
“…The finding that high MOM intake was associated with significantly better outcomes joins two recent observational cohort studies of EHM-fed VLBW infants, 2 , 3 which compared health outcomes for predominantly MOM-fed versus predominantly PDHM-fed infants. Taken together, the three studies found that predominantly MOM-fed infants had better clinical outcomes, 1 , 3 healthier microbiome colonization 1 , 2 , 3 including potential modulation of the negative impact of antibiotic exposure, 1 , 3 and improved metabolic/metabolomic profiles 2 than primarily PDHM-fed infants. Furthermore, predominantly PDHM-fed infants had slower and/or impaired growth, 1 , 3 including higher rates of head circumference measures below the third percentile, 3 higher rates of bronchopulmonary dysplasia 3 , and altered pyrimidine and steroid pathways.…”
Section: Main Textmentioning
confidence: 55%
“…Furthermore, predominantly PDHM-fed infants had slower and/or impaired growth, 1 , 3 including higher rates of head circumference measures below the third percentile, 3 higher rates of bronchopulmonary dysplasia 3 , and altered pyrimidine and steroid pathways. 2 Although these studies were limited by relatively small sample sizes and observational designs, the convergence of findings adds to clinical concerns that high-dose PDHM may be an inadequate long-term supplement for low-dose MOM in VLBW infants. These findings have important implications for future research, clinical quality improvement initiatives, and efforts to prioritize the availability of MOM in the NICU.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Preterm infants fed MOM show a significantly greater presence of Bifidobacteriaceae and a lower presence of Staphylococcaceae, Clostridiaceae, and Pasteurellaceae, compared to preterm infants fed DHM (67). Piñeiro-Ramos et al showed significant differences in the galactose, starch and sucrose metabolism pathways when comparing MOM and DHM, as well as differences in the gut microbiota composition (68). Moreover, it was shown that the protective effect of DHM is not complete probably due to destruction of the enzymes and immune molecules during pasteurization process (69,70).…”
Section: Human Milk Vs Formula Feedingmentioning
confidence: 99%
“…Throughout one’s life, microbiota can be influenced and modified by various factors, including maternal health [ 10 , 11 , 12 ], pregnancy complications, peripartum antibiotic administration [ 13 ], mode and place of delivery [ 14 ] and breastfeeding [ 11 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%